2020
DOI: 10.1088/1361-665x/abbc5a
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic and mechanical properties of conductive polyethylene composite antennas for utility location

Abstract: Location of polyethylene utility pipes is improved by installing electromagnetic targets with the pipe. A new electromagnetic target could be created by impregnating polyethylene with conductive materials to impart it with electromagnetic properties necessary for use in utility location. Antennas created from this conductive polyethylene composite could be molded directly to the pipe during fabrication. The addition of high concentrations of conductive fillers into the material alters the mechanical performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previous work has indicated that when large aluminum flakes are used as conductive filler, the flakes can act as crack initiation points, leading to premature failure relative to polyethylene with no fillers. [ 8 ]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work has indicated that when large aluminum flakes are used as conductive filler, the flakes can act as crack initiation points, leading to premature failure relative to polyethylene with no fillers. [ 8 ]…”
Section: Resultsmentioning
confidence: 99%
“…This fracture surface shows short tendrils typical to a brittle fracture surface of polyethylene compounded with carbon black. [ 8,53 ] A higher magnification image of tendrils formed during typical brittle fracture is shown in Figure 6C. A specimen with a healed fracture is shown in Figure 6E, and a higher magnification image of the same area is shown in Figure 6F.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations